Effect of Compost Fertilizer Dosage and Compost Tea on the Growth of Red Calliandra (Calliandra calothyrsus Meisn.) Seedlings - Elisa Herawati; Adelia Juli Kardika; Masrudy M; Noorhamsyah (Jurnal Loupe, 2024)
Kaliandra (Calliandra calothyrsus Meisn) is a plant capable of producing large amounts of biomass, potentially as a renewable energy source that supports the reduction of dependence on fossil fuels. The transition from fossil fuels to renewable energy is an urgent and long-term solution, as the use of fossil fuels as an energy source contributes to global warming and climate change.This study aims to evaluate the effect of compost fertilizer dosage and compost tea on the growth of height and diameter of kaliandra seedlings. Using a one-factor complete randomized design (CRD) method with treatment of compost fertilizer doses K0 (0 grams), K1 (60 grams), K2 (75 grams) and K3 (90 grams) and compost tea doses TK1 (0 ml), TK1 (50 ml), TK2 (75 ml) and TK3 (100 ml). Research results: 1. The treatment of compost doses and compost tea showed significant differences in the height growth of calliandra seedlings. 2. Compost fertilizer with a dose of 90 grams (K3) showed a better height growth rate than compost tea fertilizer with a dose of 100 ml (TK3), 75 ml (TK2), and 50 ml (TK1). 3. Compost tea fertilizer with doses of 50 ml (TK1) and 75 ml (TK2) showed a better height growth rate than compost fertilizer with doses of 60 grams (K1) and 75 grams (K2). 4. The compost fertilizer dose treatment showed a significant difference in the growth rate of Calandra seedling diameter, while the compost tea dose treatment did not show a significant difference. 5. Compost fertilizer with doses of 75 grams (K2) and 90 grams (K3) showed better diameter growth than compost tea fertilizer with doses of 75 ml (TK2) and 100 ml (TK3). 6.  The optimal dosage recommendation in this study is 90 grams of compost fertilizer and 75 ml of compost tea.